The Farmer’s Strategy in Maintaining the Sustainability of Organic Farming in Rowosari Village, Jember Regency - Mardani, Dwi; Kusumah, Maulana Surya (Jurnal ENTITAS SOSIOLOGI, 2018)
The Tani Jaya 2 farmer group is the only farming community that can develop their organic farming and survival since it was founded. As farmers who grow organic crops, they need special efforts to maintain their existence. Using a qualitative research design, researchers found that organic farmers face many challenges in managing their organic agriculture. For this reason, they must develop and ensure the sustainability of organic farming. Efforts to build farmers' knowledge in maintaining organic farming were established and influenced by the success of the strategies they used. Their plans include, firstly, empowering through the assistance of agricultural capital. Second, maintaining product quality. Third, build an external cooperation network. By relying on this effort, organic farming in Jember District can survive. Keywords: awareness construction, organic farmer strategy, organic farmer empowerment. Referensi: Basrowi. 2005. Pengantar Sosiologi. Bogor: Ghalia Indonesia. Creswell, John W. 2014. Research Design: Pendekatan Metode Kualitatif, Kuantitatif, dan Campuran. Terjemahan oleh Achmad Fawaidi & Rianayati K.P. 2016. Yogyakarta: Pustaka Pelajar. Damsar & Indriyani. 2009. Pengantar sosiologi ekonomi. Jakarta: Prenadamedia Group. Departemen Pendidikan dan Kebudayaan. 1991. Kamus Besar Bahasa Indonesia. Jakarta: Balai Pustaka. Harker, R., Mahar, C., dan Wilkes, Chris. 1990. (Habitus X Modal) + Ranah = Praktik: Pengantar Paling Komprehensif kepada Pemikiran Pierre Bourdieu. Terjemahan oleh Pipit Maizier. Yogyakarta: Jalasutra. Henslin, James M. 2006. Sosiologi dengan Pendekatan Membumi (6 ed.). (W. Hardani, B. A. Yoso, Eds., & K. Sunarto, Trans.). Jakarta: Erlangga Khotimah, Aidah Chusnul. 2016. Konstruksi Pengetahuan Tentang Pertanian Organik Pada Petani Desa Wates Kabupaten Tulungagung. Skripsi. Jember: Sosiologi. Fakultas Ilmu Sosial dan Ilmu Politik. Universitas Jember. Moleong, Lexi J. 2000. Metode Penelitian Kualitatif. (Tjun Sujarman, (Ed.). Bandung: PT. Remaja Rosdakarya. Mubarok, J. Ifnul. 2012. Kamus Istilah Ekonomi. Bandung: Yrama Widya Pribadi, Deki. 2016. Strategi Kelompok Tani Mandiri dalam Mewujudkan Pertanian Organik dan Wisata Organik di Desa Lombok Kulon Kecamatan Wonosari Kabupaten Bondowoso. Skripsi. Jember: Sosiologi. Fakultas Ilmu Sosial dan Ilmu Politik. Universitas Jember. Ritzer, George dan Goodman, D. J. Teori Sosiologi Modern. Terjemahan Oleh Alimandan. 2003. Jakarta: Kencana. Soekanto, Soerjono. 1983. Kamus Sosiologi. Jakarta: CV. Rajawali. Soetriono. 1993. Dasar Ilmu Pertanian. Fakultas Pertanian Universitas Jember. Sutanto, Rachman. 2002. Pertanian Organik: Menuju Pertanian Alternatif dan Berkelanjutan. Yogyakarta: Kanisius. Universitas Jember. 2012. Pedoman Penulisan Karya Ilmiah. Jember: Jember University Press. Internet: Firli, Andhika. 2013. Revolusi Hijau dan Dampak Buruknya. http://www.kompasiana.com/firlianggara/revolusi-hijaudandampakburuknya_552e08686ea8345b248 b457b. diakses tanggal 03 Oktober 2016.